Metagenomics Reveals the Microbial Community Responsible for Producing Biogenic Amines During Mustard [Brassica juncea (L.)] Fermentation - Yu, Yangyang; Li, Lu; Xu, Yujuan; Li, Hong; Yu, Yuanshan; Xu, Zhenlin (Frontiers in Microbiology, 2022)
Biogenic amines (BAs) are considered potential hazards produced during fermented food processing, and the production of BAs is closely related to microbial metabolism. In this work, the changes of BA content were analyzed during mustard fermentation, and microbes and gene abundance responsible for producing BAs were revealed by metagenomic analyses. The results showed that cadaverine, putrescine, tyramine, and histamine were generated during mustard fermentation, which mainly accumulate in the first 6 days of fermentation. According to the metagenome sequencing, the predominant genus was Bacillus (64.78%), followed by Lactobacillus (11.67%), Weissella (8.88%), and Leuconostoc (1.71%) in the initial fermentation stage (second day), while Lactobacillus (76.03%) became the most dominant genus in the late stage. In addition, the gene abundance of BA production enzymes was the highest in the second day and decreased continuously as fermentation progressed. By tracking the source of the enzyme in the KEGG database, both Bacillus and Delftia closely correlated to the generation of putrescine. Besides, Bacillus also correlated to the generation of tyramine and spermidine, and Delftia also correlated to the generation of cadaverine and spermine. In the processes of fermentation, the pH of fermented mustard showed slower decrease compared with other similar fermented vegetables, which may allow Bacillus to grow at high levels before the pH <4. This study reveals the change of BA content and microbes involved in BA formation during mustard fermentation.